History of The Economic Development of Rice Field Farmers in Palasa Tangki Village 2014-2023 - Y. Abbas, Nurfadillah; Juraid; Lukman; Ismail (Kirana Publisher (KNPub), 2025)
This study discusses: 1. The history of the formation of Palasa Tangki village, 2. The economic development of the rice farming community, 3. The efforts of the village government in developing the agricultural sector as the main supporter of the village economy. The type of research used is historical research with an economic approach, data collection techniques in this study include: Observation, interviews, documentation and writing (historiography). The results of this study indicate that the journey and economic development of rice farmers in Palasa Tangki village over the past ten years experienced a turning point that occurred in 2015 when the village government began to introduce modern agricultural technology such as tractors, water pumps, superior seeds, and provided training and fertilizer assistance to farmers. This modernization has had a positive impact on increasing crop yields, expanding market access, and community welfare, as indicated by the increasing number of farming families who are able to send their children to school outside the area. This study confirms that the agricultural sector remains the backbone of the village economy and requires special attention in terms of protection, empowerment, and infrastructure development to support the welfare of the farming community in a sustainable manner.